2006
DOI: 10.1177/1363459306061785
|View full text |Cite
|
Sign up to set email alerts
|

Medical doctors and complementary and alternative medicine: the context of holistic practice

Abstract: Consumers, health care financing, external and internal competition are factors identified in the medical literature as prompting change within medicine. I test these factors to determine if they also prompt regular doctors to define themselves as 'holistic MDs' and align themselves with complementary and alternative medicine (CAM). State-level regression analyses on the number of MDs advertising in referral directories for CAM therapies find holistic practice a function of practice locale. The proportion of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This identifies some areas of concern, especially with the GPs’ opinions tending towards neutrality on this issue. In contrast, recent American findings suggest that health professionals are becoming more sensitive to patients’ use of CAM, some even calling themselves ‘holistic’ in order to attract more clients (51, 52). Pharmacists were perceived by the majority of the other participants as insufficiently informed about CAM, and pharmacists’ own opinions tended towards neutrality.…”
Section: Discussionmentioning
confidence: 97%
“…This identifies some areas of concern, especially with the GPs’ opinions tending towards neutrality on this issue. In contrast, recent American findings suggest that health professionals are becoming more sensitive to patients’ use of CAM, some even calling themselves ‘holistic’ in order to attract more clients (51, 52). Pharmacists were perceived by the majority of the other participants as insufficiently informed about CAM, and pharmacists’ own opinions tended towards neutrality.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, interestingly, it has been shown that doctors tend to be uncomfortable about collaborating with CAM practitioners even when they work in the same hospital teams [43]. On the other side of the spectrum, an American study indicated that some family doctors preferred to call themselves 'holistic' and align themselves with CAM in order to attract more consumers [44]. Further, it has been found that doctors sometimes tend to report high acceptance of CAM, even though their knowledge of them was, self-reportedly, quite poor, creating a potentially dangerous situation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Medicine implies complementary and alternative medicine, while holistic nursing means to view all a patients' aspects in the present situation [7,8]. In their study from 1987 Goldstein et al investigated differences between Holistic Physicians (HP) (members of the American Holistic Medical Association) and Family Physicians (FP).…”
Section: Introductionmentioning
confidence: 99%